The capsaicin receptor TRPV1 reduces sepsis-associated brain injury in mice by inhibiting pyroptosis - Long, Menghong; Hu, Zhenyu; Long, Feiyu; Chen, Yingxu; Liu, Li; Wang, Maohua (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2025)
Purpose Sepsis is a life-threatening disorder marked by organ dysfunction due to infection. Transient receptor potential vanilloid 1 (TRPV1) is a non-selective, ligand-gated cation channel activated by multiple stimuli. This study investigates the role of TRPV1 in sepsis-associated encephalopathy (SAE). Methods The SAE models of wild-type and TRPV1 knockout (TRPV1 -/- ) mice were established through intraperitoneal injection of 10 mg/kg lipopolysaccharide. Brain tissues and serum were collected 24 h post-injection for analysis. Rectal temperature was monitored at 12 and 24 h, and the 7-day survival rate was recorded. Mice were pretreated with capsaicin (CAP), and brain tissue and serum were collected for detection. Results TRPV1 expression was significantly elevated in the brain tissues of mice with sepsis. TRPV1 -/- aggravated SAE symptoms, as evidenced by a significant decrease in rectal temperature, a reduced 7-day survival rate, an elevated Murine Sepsis Score, and greater impairment in learning and memory. Mechanistically, TRPV1 deficiency increased NF-κB, pyroptosis-related proteins, and levels of IL-6 and TNF-α in SAE mice. CAP pretreatment significantly reduced abnormal neurons in the CA1 region, decreased NF-κB, Pro-caspase1, and Cleaved-caspase1 in brain tissues, and lowered IL-1β and IL-18 serum levels, with this effect being TRPV1-dependent. Conclusion In summary, TRPV1 deficiency worsens SAE-induced damage in mice, associated with activation of NF-κB and pyroptosis pathways. CAP pretreatment improved the damage caused by SAE by activating TRPV1.